MENTAL HEALTH STATUS OF B.ED. STUDENT TEACHERS OF COLLEGES OF TEACHER EDUCATION IN MANIPUR - Devi, Chongtham Beda; Sonia, Chanam Sonia; Sonia, Soram; Singh, Anilkumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Mental Health is a Universal Human Right. Everyone has a right to the highest attainable standard of mental health. This includes the right to be protected from mental health risks, good quality care, the right to liberty, independence and inclusion in the community. A mentally healthy and well-adjusted student, teachers can adjust very easily to cope with the daily life challenges effectively. The role of teachers in teaching learning is utmost important in bringing effectiveness and quality in transecting teaching learning process. A teacher of mentally sound possesses emotional stability and willingness to teach effectively inside the classroom and also inculcate good study habits among the students. The present study aims to focus to compare the mental health status of male and female and also compare the mental health status of rural and urban B.Ed. student teachers. A standardized Mental Health Inventory (HMI) developed by Jagdish & Srivastava (1983) is used to measure the mental health of student teacher in 6 (six) Teacher Education Colleges under Manipur University with 300 B.Ed. student teacher by using simple random sampling technique. The result reveals that (I) majority of the B.Ed. student teachers, that is 72% of them possess an average level of mental health status. (II) No significant difference between male and female student teachers in terms of their mental health status and (III) Student teachers residing in rural and urban teacher are similar in relation to their mental health